A comparative double-blind randomized study on the effectiveness of Duloxetine and Gabapentin on painful diabetic peripheral polyneuropathy - Majdinasab N; Kaveyani H; Azizi M (Dove Medical Press, 2019)
Nastaran Majdinasab,1 Hossein Kaveyani,2 Mojgan Azizi31Musculoskeletal Rehabilitation Research Center, Jundishapur University of Medical Sciences, Ahvaz, Iran; 2Department of Neurology, Golestan Hospital, Ahvaz Jundishapur University of Medical Sciences, Ahvaz, Iran; 3Department of Pediatrics, Golestan Hospital, Ahvaz Jundishapur University of Medical Sciences, Ahvaz, IranBackground: The most common cause of polyneuropathy is diabetes mellitus. Neuropathic pain is seen in 26% of diabetic population. Therapeutic techniques for this disease can become challenging.Method: This study was a prospective comparative double-blind randomized study which was conducted during an eight-week period. Totally, 104 painful diabetic peripheral polyneuropathy (PDPP) patients who had a minimum Visual Analog Scale (VAS) of 40 millimeters, received no pain-controlling medication, and had no other severe disease at its final stage were randomly assigned to two groups (n=52) through the four block method. One group received Duloxetine and the other received Gabapentin. The effectiveness was measured through primary effectiveness (VAS scale) and secondary effectiveness (Sleep Interference Score, and Clinical Global Impression of Change (CGIC)). Medication compliance was assessed by enumerating the number of patients who refused treatment because of side effects. The Fisher’s exact T-test and ANOVA were used for data analysis. This study was approved by the Ethics Committee of Jundishapur, University of Medical sciences Ahvaz, Iran, under reference number: IR.AJUMS.REC.1395.78. In addition, this study was registered and approved in the Iranian Registry of Clinical Trials (IRCT ID: IRCT20161023030455N2) (http://irct.ir/).Results: VAS, Sleep Interference Score, and CGIC were significantly improved (P<0.05) through time in both groups, [For GBP: VASBaseline,=64±20.03, VASweek1,=55.32±18.76, VASweek4,=44.68±15.82, VASweek8,=39.43±14.32; For DLX: VASBase-line,=62±21.18, VASweek1,=58.76±20.37, VASweek4,=45.84±16.21, VASweek8,=36.78±15.62] while a significant difference between the two groups was not observed (P<0.05). However, such significant improvements were not observed in the Duloxetine group at the end of the first week (P=674). Improvement in Sleep Interference Score and CGIC were similar to the results for the VAS scale. Side effects in the Duloxetine group (n=2) compared to the Gabapentin group (n=9) were significantly less (P<0.001). As a result, medication acceptance in the Duloxetine group (n=47) was significantly better than the Gabapentin (n=41) group (P<0.001).Conclusion: Both Duloxetine and Gabapentin are effective for the treatment of PDPP. On the one hand, Gabapentin shows the effect earlier while has more side effects. Conversely, Duloxetine has better medication compliance.Trial registration: The method of this study was approved by the Ethics Committee of Jundishapur University of Medical Sciences, Ahvaz, Iran, under reference number: IR.AJUMS.REC.1395.78. In addition, this study was registered and approved in the Iranian Registry of Clinical Trials (IRCT ID: IRCT20161023030455N2) (http://irct.ir/).Keywords: Duloxetine, Gabapentin, painful diabetic peripheral neuropathy